Effect of Desmopressin on Platelet Aggregation and Blood Loss in Patients Undergoing Valvular Heart Surgery - Lei Jin; Hong-Wen Ji (Chinese Medical Journal, 2015)
Background: Blood loss after cardiac surgery can be caused by impaired platelet (PLT) function after cardiopulmonary bypass. Desmopressin or 1-deamino-8-D-arginine vasopressin (DDAVP) is a synthetic analog of vasopressin. DDAVP can increase the level of von Willebrand factor and coagulation factor VIII, thus it may enhance PLT function and improve coagulation. In this study, we assessed the effects of DDAVP on PLT aggregation and blood loss in patients undergoing cardiac surgery. Methods: A total of 102 patients undergoing valvular heart surgery (from October 2010 to June 2011) were divided into DDAVP group (n = 52) and control group (n = 50). A dose of DDAVP (0.3 μg/kg) was administered to the patients intravenously when they were being re-warmed. At the same time, an equal volume of saline was given to the patients in the control group. PLT aggregation rate was measured with the AggRAM four-way PLT aggregation measurement instrument. The blood loss and transfusion, hemoglobin levels, PLT counts, and urine outputs at different time were recorded and compared. Results: The postoperative blood loss in the first 6 h was significantly reduced in DDAVP group (202 ± 119 ml vs. 258 ± 143 ml, P = 0.023). The incidence of fresh frozen plasma (FFP) transfusion was decreased postoperatively in DDAVP group (3.8% vs. 12%, P = 0.015). There was no significant difference in the PLT aggregation, urine volumes, red blood cell transfusions and blood loss after 24 h between two groups. Conclusions: A single dose of DDAVP can reduce the first 6 h blood loss and FFP transfusion postoperatively in patients undergoing valvular heart surgery, but has no effect on PLT aggregation.